Burnout ieri e oggi: stato delle conoscenze / Burnout: survey of the literature - Camerino, Donatella; Cassitto, Maria Grazia; Gugiari, Maria Chiara; Conway, P.M. (La Medicina del Lavoro, 2013)
Summary«Burnout: survey of the literature». Background: Past clinical research has provided varied and sometimes diverging descriptions of burnout. Objectives: As burnout is still prevalent in today’s workplaces, actions are required mainly at the primary but also at the secondary and tertiary levels of prevention. Methods: In this literature review, the concept of burnout is reread through the lens of positive psychology and the most established theoretical models in the field. Results: A common view is seemingly emerging that characterizes burnout as a condition of alienation, loss of motivation and low autonomy resulting from an unbridgeable gap in the personal and/or organizational resources that one has to invest in building a stimulating and rewarding professional career, full of significant relationships that give meaningfulness to one’s life project. Conclusions: Establishing clinical criteria for burnout, as it is the case in some European countries, could facilitate the identification of the syndrome and the estimation of its prevalence in Italian work organizations.RiassuntoIntroduzione: La letteratura riporta diverse e, a volte discordanti, descrizioni teoriche e cliniche del fenomeno del burnout. Obiettivi: La prevenzione di questa sindrome rientra, oggi, a livello primario, in quella dello stress lavoro-correlato. Considerata la sua frequenza, va tuttavia affrontata anche a livello di prevenzione secondaria e terziaria. Metodi: Il concetto di burnout è stato riletto alla luce della psicologia positiva e dei modelli teorici oggi più accreditati. Risultati: Una visione aggiornata, caratterizza questa sindrome come uno stato di alienazione, una perdita di motivazione e di autonomia in conseguenza di un’irrimediabile mancanza di risorse personali e/o organizzative da investire in un percorso professionalmente interessante, gratificante e con relazioni significative tali da infondere valore e spessore al personale progetto di vita. Conclusioni: la scelta di criteri per la definizione clinica di burnout come già avviene in alcuni paesi europei potrebbe favorire un riconoscimento della patologia e studi di prevalenza nelle diverse realtà lavorative italiane.